2022
DOI: 10.1093/gji/ggac255
|View full text |Cite
|
Sign up to set email alerts
|

Post-seismic motion after 3 Chilean megathrust earthquakes: a clue for a linear asthenospheric viscosity

Abstract: Over the last decade, three major subduction earthquakes, Maule Mw 8.8 (2010), Illapel Mw 8.3 (2015) and Iquique Mw 8.1 (2014), occurred in Chile and generated significant post-seismic deformations. These large scale and long lasting deformations can be quantified with modern GNSS precise positioning and highlight visco-elastic processes in the asthenosphere. Here, we calculate the ratios of cumulative post-seismic displacements after 5 years over the co-seismic offsets. We find that at any distance from the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The tectonic context in Atacama, in the interseismic phase about a century after the latest major earthquake, was favorable to detect the SSE2014 by survey GPS. In contrast, regions like Navidad (34.8°S) or Los Vilos (32°S), where swarms regularly occur, are strongly affected by the postseismic deformations following the 2010 Maule and 2015 Illapel earthquakes [Klein et al, 2016;Boulze et al, 2022]. In such a context, the survey GPS can not compensate for the low density of continuous stations.…”
Section: Sses Elsewhere In Chilementioning
confidence: 99%
“…The tectonic context in Atacama, in the interseismic phase about a century after the latest major earthquake, was favorable to detect the SSE2014 by survey GPS. In contrast, regions like Navidad (34.8°S) or Los Vilos (32°S), where swarms regularly occur, are strongly affected by the postseismic deformations following the 2010 Maule and 2015 Illapel earthquakes [Klein et al, 2016;Boulze et al, 2022]. In such a context, the survey GPS can not compensate for the low density of continuous stations.…”
Section: Sses Elsewhere In Chilementioning
confidence: 99%
“…Most recently, Boulze et al. (2022) suggested that a mantle viscosity of ∼5 × 10 18 Pa s produced the right order of magnitude of postseismic displacements following the 2014 Iquique and 2015 Illapel events. Based on the absence of time and spatial variation in the ratio of postseismic to coseismic displacements, they argued that a Maxwell viscosity model was preferred to a power law viscosity.…”
Section: Discussionmentioning
confidence: 99%
“…Over 2010–2015, three subduction earthquakes, Maule M w 8.8, Illapel M w 8.3 and Iquique M w 8.1 occurred in Chile and generated significant postseismic deformation (e.g., Boulze et al., 2022) (Figure 7). Among them, the largest and the most studied event was the 2010 Maule earthquake, central Chile (Bedford et al., 2016; Sun et al., 2018; Weiss et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because PSR studies are generally sensitive to the viscosity of the uppermost sublithospheric mantle (perhaps only ~ 10 km or so), these low values are not inconsistent in any obvious way with, e.g., the Fennoscandian rebound results discussed above, as per the restrictions implied by the Ct scaling. Also, Boulze et al 28 have recently concluded that the asthenosphere responds to large subduction zone earthquakes via linear (Newtonian) rheology, as opposed to power-law rheology.…”
mentioning
confidence: 99%